Studying adoption of internet banking in Ampang / Che Ahmad Izzatullah Che Yaacob - Che Yaacob, Che Ahmad Izzatullah (2015)
The aim of the study is to examine what are the factors that influencing the adoption of internet banking in context Malaysian users. Dimensions such as trust, security, complexity and privacy had been examined. A total of 100 useable questionnaires was coded and analyzed using IBM SPSS Statistic 20 software. Statistical methods like validity testing, descriptive analysis, frequencies analysis, hypotheses testing and regression analysis were used in this research. The regression results from a survey involving 100 respondents in Ampang have shown that user’s trust and privacy have highest significance towards the adoption of internet banking in Malaysia. Both of them are having strong relationship with adoption of internet banking. Another two independent variables which are complexity and security did not have significant relationship in this study